2014
DOI: 10.3748/wjg.v20.i45.17065
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hepatic blood flow and liver function in alcoholic liver cirrhosis

Abstract: Our investigation showed that there is a close correlation between liver function and hepatic blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Before initiation of ECMO, ultrasonography confirmed adequate filling in the right hepatic artery and the portal vein. The right hepatic arterial blood flow (HAF) and the portal venous blood flow (PVF) had no significant difference from the normal reference level (Table ). After initiation of ECMO, the hepatic artery and the portal vein filling was poor at the ECMO perfusion level of <2.0 L/minute, but it was satisfactory at 2.0 to 3.0 L/minute.…”
Section: Resultsmentioning
confidence: 93%
“…Before initiation of ECMO, ultrasonography confirmed adequate filling in the right hepatic artery and the portal vein. The right hepatic arterial blood flow (HAF) and the portal venous blood flow (PVF) had no significant difference from the normal reference level (Table ). After initiation of ECMO, the hepatic artery and the portal vein filling was poor at the ECMO perfusion level of <2.0 L/minute, but it was satisfactory at 2.0 to 3.0 L/minute.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, obstruction occurs in the whole process from cholesterol synthesis to plasma lipoproteins processing and assembling, and the level of TC is much lower than that of normal condition (18,19). Meanwhile, liver is also the main place for human protein metabolism, and can synthesize amino acid into protein that human body needs, such as ALB (20). Once ALB is synthesized in rough surfaced endoplasmic reticulum of hepatic cells, it is secreted to sinus hepaticas by Golgi body.…”
Section: Resultsmentioning
confidence: 98%
“…There were 15 patients with nonalcoholic fatty liver (NAFL) who had no fibrosis and inflammatory cell infiltration. The patients with NASH were evaluated on the basis of Brunt’s classification [ 21 , 46 , 47 ], while those with CHC were evaluated on the basis of Desmet’s classification [ 22 ]. Staging fibrosis in NASH based on Brunt’s classification: Stage 1: zone 3 perivenular perisinusoidal/pericellular fibrosis, focal or extensive; Stage 2: as above with focal or extensive periportal fibrosis; Stage 3: bridging fibrosis, focal or extensive; and Stage 4: cirrhosis.…”
Section: Methodsmentioning
confidence: 99%
“…However, few reports have addressed the association between HBF and liver function; no report has examined the progression of liver function according to the etiology of CLD. Moreover we previously reported that hepatic TBF in patients with liver cirrhosis varied according to the etiology of the disease and there is a close correlation between liver function and hepatic blood flow in patients with alcoholic liver cirrhosis [ 21 , 22 ]. In the present study, we investigated the difference in the fibrosis markers between patients with initial chronic hepatitis and those with advanced chronic hepatitis in NASH and CH-C.…”
Section: Introductionmentioning
confidence: 99%